DHARMA, DUTY AND DEVOTION: EXPLORING MARITAL INSTITUTION IN RAMAYANA AND MAHABHARATA - Singh, Prikshit (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The examination of marital unions in the Ramayana and the Mahabharata, two renowned Indian epics, presents a captivating analysis of the institution of marriage throughout ancient times in India. This research paper explores the portrayal of marriages in epic narratives, providing insights into the many viewpoints, beliefs and societal conventions related to marital unions within Indian culture. The Ramayana prominently features the concept of marriage, as seen by the sacred bond formed between Rama and Sita. This marital union is frequently regarded as the quintessence of an exemplary matrimony, highlighting steadfast affection, dedication and moral excellence. The unwavering faithfulness exhibited by Sita throughout her period of banishment, along with Rama's unwavering dedication to her despite encountering several challenges, serves as a compelling demonstration of the deep connection inherent in a matrimonial union. The Mahabharata presents a comprehensive and varied portrayal of the institution of marriage. The epic encompasses polygamous relationships, partnerships within families and intricate dynamics inside marriages. The matrimonial union between Draupadi and Arjuna, characterized by the Swayam Var ceremony and subsequent practice of polyandry, presents a departure from established societal conventions. The matrimonial unions between Kunti and Pandu, as well as the alliances formed between different royal lineages, serve to emphasize the political and dynastic aspects inherent in the institution of marriage. Furthermore, the figure of Draupadi serves as a representation of the resilience and empowerment of women within the framework of marriage relationships.